IBM z/OS V2R2 communications server TCP/IP implementation : volume 3 high availability, scalability, and performance - White, Bill (Telecommunications engineer) (IBM redbooks., 2016)
For more than 50 years, IBM® mainframes have supported an extraordinary portion of the world's computing work, providing centralized corporate databases and mission-critical enterprise-wide applications. IBM z Systems™ platform, the latest generation of the IBM distinguished family of mainframe systems, has come a long way from its IBM System/360 heritage. Likewise, its IBM z/OS® operating system is far superior to its predecessors in providing, among many other capabilities, world-class and state-of-the-art support for the TCP/IP protocol suite. TCP/IP is a large and evolving collection of communication protocols managed by the Internet Engineering Task Force (IETF), an open, volunteer organization. Because of its openness, the TCP/IP protocol suite has become the foundation for the set of technologies that form the basis of the Internet. The convergence of IBM mainframe capabilities with Internet technology, connectivity, and standards (particularly TCP/IP) is dramatically changing the face of information technology and driving requirements for even more secure, scalable, and highly available mainframe TCP/IP implementations. The IBM z/OS Communications Server TCP/IP Implementation series provides understandable, step-by-step guidance for enabling the most commonly used and important functions of z/OS Communications Server TCP/IP. This IBM Redbooks® publication is for people who install and support z/OS Communications Server. It starts with a discussion of virtual IP addressing (VIPA) for high-availability, with and without a dynamic routing protocol. It describes several workload balancing approaches with the z/OS Communications Server. It also explains optimized sysplex distributor intra-sysplex load balancing. This function represents improved application support using optimized local connections together with weight values from extended Workload Manager (WLM) interfaces. Finally, this book highlights important tuning parameters and suggests parameter values to maximize performance in many client installations.